Ethanol Extract of Grass Jelly Leaves: Bioactive Analysis and In silico Study on Estrogen Receptor Alpha Related to MCF-7 Breast Cancer - Irpani, Abdul Mulki; Yuliantini, Anne; Bintang, Muhammad Ilham; Sella, Arinda Tri Pramay; Sodik, Jajang Japar (Sciences of Pharmacy, 2026)
Breast cancer is a major cause of mortality among women and requires the development of alternative therapies derived from natural products. This study aimed to profile bioactive compounds in the ethanol extract of gras jelly leaves (Cyclea barbata Miers) and evaluate their predicted interactions with estrogen receptor alpha (ERα), a key regulator of proliferation in ER-positive MCF-7 breast cancer cells using an in silico approach. LC–HRMS analysis followed by database matching tentatively annotataed 44 major compounds based on peak intensity after data filtering. Molecular docking and simulation results indicated that several compounds exhibited favorable predicted binding affinity toward estrogen receptor targets. Among them, (3β,24R,24′R)-fucosterol epoxide demonstrated the most stable interaction. These findings suggest that the compound showed promising interaction stability toward the estrogen receptor in computational analysis. However, further in vitro and in vivo studies are required to validate its biological activity.